Who does the shopping? German time-use evidence, 1996 - 2009 - Vivien Procher; Colin Vance (University of Wuppertal, Schumpeter School of Business and Economics, 2013)
The labor force participation rate of women and men is converging in industrialized countries, but disparities nevertheless remain with respect to unpaid activities. Shopping for household maintenance, in particular, is a time-consuming, out-of-home activity that continues to be undertaken primarily by women, irrespective of their employment status. The present study employs panel methods to analyze, descriptively and econometrically, gender disparities in shopping behavior among couples using data from the German Mobility Panel (MOP) for 1996 to 2009. While women still shop more than men, we find evidence that the differential has narrowed in recent years, particularly among couples with children. Several individual and household characteristics are found to be significant determinants of shopping behavior, whereby employment status and children emerge as the most important single factors. In addition, the possession of a driver's license coupled with unrestricted car availability increase each partner's time in shopping.
urn:nbn:de:hbz:468-20130121-122642-2
Keywords: D13; J16; 330; Shopping; Time-use; gender differences